Features of Civil Society Institutions: International Experience (International relations and international law Journal, 2023)
Today, the concept of civil society in the country is presented in this article from a modern point of view, at the political, social, international, and international levels, other values ​​of civil life, democratic laws, separation of powers, legal opposition, multi-party system, people, associations, groups, political and social freedoms, etc. Criticism is very valuable and has been studied through topical issues.The author of the article correctly described international experience of the features of civil society institutions in a scientific manner from the point of view of ideological pluralism, structural and psychological, socio-political.In the scientific-methodological section, the author described the institutions of civil society from the ancient times, combined with the present day, based on the data of the works of European and American sociologists and from the point of view of modern postmodernism, using the historical methodology.Today, in our country, this problem is studied as a trend in the scientific works and articles of various Kazakhstani, Russian, Western and Eastern scientists. However, taking into account the fact that there are various conflicting opinions about the idea of ​​civil society, the concept of civil society as self-governing non-governmental organizations from the 17th-18th centuries from a historical and scientific point of view: Adam Smith, David Ricardo, Hegel, Habermas, T. Hobbes, Marx, Gramsci, S. Montesquieu, J. J. Rousseau, T. Payne, I. Bentham, Wilhelm Humbold, A. Michnik, N. Bobbio, J. Analysis based on Habermas research is very relevant. Based on the researches that studied this issue from a new angle, the article made its own critical political analysis.In considering the institutional features of civil society, it considers associations, family, cooperatives, social organizations, professional, creative, sports, ethnic, industrial and individual life as an association that protects human rights, illuminates social harmony, and realizes and controls the interests of citizens.Key words: civil society, bourgeois society, market relations, democratic laws, separation of powers, legal opposition, pluralism